Sensitivity of cold acclimation to elevated autumn temperature in field-grown Pinus strobus seedlings - Chang, Christine Y.; Unda, Faride; Zubilewich, Alexandra; Mansfield, Shawn D.; Ensminger, Ingo (Frontiers in Plant Science, 2015)
Climate change will increase autumn air temperature, while photoperiod decrease will remain unaffected. We assessed the effect of increased autumn air temperature on timing and development of cold acclimation and freezing resistance in Eastern white pine (EWP, Pinus strobus) under field conditions. For this purpose we simulated projected warmer temperatures for southern Ontario in a Temperature Free-Air-Controlled Enhancement (T-FACE) experiment and exposed EWP seedlings to ambient (Control) or elevated temperature (ET, +1.5°C/+3°C during day/night). Photosynthetic gas exchange, chlorophyll fluorescence, photoprotective pigments, leaf non-structural carbohydrates (NSC), and cold hardiness were assessed over two consecutive autumns. Nighttime temperature below 10°C and photoperiod below 12h initiated downregulation of assimilation in both treatments. When temperature further decreased to 0°C and photoperiod became shorter than 10h, downregulation of the light reactions and upregulation of photoprotective mechanisms occurred in both treatments. While ET seedlings did not delay the timing of the downregulation of assimilation, stomatal conductance in ET seedlings was decreased by 20-30% between August and early October. In both treatments leaf NSC composition changed considerably during autumn but differences between Control and ET seedlings were not significant. Similarly, development of freezing resistance was induced by exposure to low temperature during autumn, but the timing was not delayed in ET seedlings compared to Control seedlings. Our results indicate that EWP is most sensitive to temperature changes during October and November when downregulation of photosynthesis , enhancement of photoprotection, synthesis of cold-associated NSCs and development of freezing resistance occur. However, we also conclude that the timing of the development of freezing resistance in EWP seedlings is not affected by moderate temperature increases used in our field experiments.